Role of ICAM1 in tumor immunity and prognosis of triple-negative breast cancer - Zhou, Qin; Xu, Jiawei; Xu, Yan; Sun, Shaokun; Chen, Jian (Frontiers in Immunology, 2023)
Treating triple-negative breast cancer (TNBC) is a difficult landscape owing to its short survival times and high risk of metastasis and recurrence among patients. Although involved in tumor invasion and metastasis, the mechanism of action of intercellular adhesion molecule 1 (ICAM1), a transmembrane glycoprotein, in TNBC is ambiguous. We examined ICAM1's role in TNBC, focusing on its expression, cell survival, mutation, and tumor immunity. ICAM1 was found to be involved in leukocyte cell adhesion, motility, and immune activation. Patients with low-ICAM1 group had shorter disease-free survival (DFS) than those with high-ICAM1 group. The group with elevated levels of ICAM1 exhibited significantly increased levels of T-cell regulation, quiescence in natural killer (NK) cells, and M1 macrophage. ICAM1 expression was correlated with immune checkpoint drugs. Then, a risk score model was created utilizing co-expressed genes associated with ICAM1. The prognostic ability of the risk score model was found to be superior to that of individual genes. According to their respective risk scores, we divided patients into high-and low-risk groups. Patients categorized as highrisk exhibited elevated clinical stages, showed higher M1 macrophage numbers, and were able to benefit better from immunotherapy. Individuals belonging to the high-risk group exhibit significantly elevated mutation rates in TP53, TTN, and SYNE1 genes, along with increased TMB and PD-L1 levels and decreased TIDE scores. These findings suggest that immunotherapy may be advantageous for the high-risk group. Furthermore, low expression of ICAM1 was found to promote polarization to M2 macrophages along with T-cell exhaustion. In conclusion, Low ICAM1 expression may be related to immune escape, leading to poor treatment response and a worse prognosis.